Desarrollo de licores macerados de fruta, con un sistema de comercialización no tradicional con mejora de procesos en la Empresa Ron Catan - Ortiz Ramírez, Guillermo Andrés (2014)
The Ecuadorian liquor industry in recent years has had several changes and skills, given the various problems that have arisen such as fraud underground enterprises; low quality of Ecuadorian products, compared to imported liquor has encouraged market entry Ecuadorian rum, vodka, and other liquors whisky from Central America, United States, Europe and other countries, which traditionally produce such beverages this has created in the Ecuadorian market competition of imported liquors have virtually displaced the Ecuadorian alcohol. Given this fact and as a protective measure, the Ecuadorian State in 2011 produces a new table of tariffs on imported liquor, basing their calculations on the alcohol content of each drink. Thus the retail prices reached in many cases tripled, reducing the importation of alcoholic beverages and encouraged domestic liquor consumption; however, the lack of quality of these products required the Ecuadorian industry to improve processes and innovate technologies to thereby meet the current needs of the Ecuadorian liquor market. With this background, and given the opportunity to compete Spirits Plant Ron Catan, you want to reactivate it works, and it plans to develop a new product in the market of Quito; will apply for marketing a nontraditional method to ensure it reaches the end customer.